Synthesis of New Bismaleimide Homopolymer and Copolymers Derived from 4, 4ˉ-Bis[4-(N-maleimidyl) Phenyl Schiff Base] Tolidine - Mustafa Salah Hasan; Al-Azzawi , Ahlam Marouf (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Polyimides are widely used in high-temperature plastics, adhesives, dielectrics, photoresists, nonlinear optical materials, separation membrane materials, and Langmuir-Blodgett (LB) films. They are commonly regarded as the most heat-resistant polymers. This work involved the synthesis of a new bismaleimide homopolymer and copolymer by performing many steps. The synthesis of compound (1) (bis [4-(amino phenyl) Schiff base] tolidine) via condensation of o-tolidine with two moles of 4-aminoacetophenone. Secondly, compound (1) was combined with maleic anhydride to form compound (2) (4, 4ˉ-bis[4-(N-maleamic acid) phenyl Schiff base] toluidine). Thirdly, a dehydration reaction was carried out affording compound (3) (4,4ˉ-bis [4-(N-maleimidyl) phenyl Schiff base] toluidine). Compound (3) represents the new vinylic monomer, which was successfully introduced in addition to homopolymerization and copolymerization with selected vinylic monomers, affording homopolymer (4) and copolymers (5, 6), respectively. The new homopolymer and copolymers showed good fusibility and solubility in many organic solvents, leading to easy processing and expected to serve a broad spectrum of applications.